TYPOLOGY OF ENTERPRISE DIGITAL TRANSFORMATION STRATEGIES IN THE CONTEXT OF RISK RESILIENCE MANAGEMENT (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2025)
In the rapidly evolving landscape of Industry 4.0 and 5.0, digital transformation has shifted from being a competitive advantage to a fundamental imperative for business survival. However, empirical evidence suggests a growing "digital vulnerability paradox," where accelerated technological adoption without a corresponding evolution in risk management systems leads to operational fragility rather than efficiency. Consequently, this paper addresses the critical scientific and practical problem of justifying a typology of digital transformation strategies through the lens of risk resilience management. The study employs a structural-logical approach to synthesize two key dimensions: the intensity of digital innovation and the depth of risk resilience integration. By analyzing the differentiation of strategies, the authors propose a multi-dimensional matrix that correlates organizational architecture levels with functional domain coverage. Based on this framework, the research identifies and characterizes four distinct strategic archetypes of digital transformation. The "Defensive Strategy" focuses on maintaining current positions and protecting assets through isolated risk management practices, primarily located within IT departments. The "Adaptive Strategy" is characterized by flexible, iterative implementation of changes with cross-functional coordination, allowing for tactical adjustments. The "Proactive Strategy" utilizes "predictive intelligence" to identify threats early and convert them into strategic insights. Finally, the "Transformational Strategy" represents the highest level of maturity, where risk resilience acts as a driver for value creation, involving a fundamental rethinking of the business model. A significant theoretical contribution of the study is the conceptualization of risk resilience levels – ranging from operational and fragmented to strategic and systemic. The authors argue that high-level strategies require the formation of specialized dynamic capabilities, such as an adaptive response architecture and strategic transformation ability. Furthermore, the paper introduces the Digital Value Resilience Ratio (VRR), a mathematical formalization designed to measure the relationship between preserved value and newly created value relative to the initial value at risk. This metric quantitatively validates the shift from a risk-avoidance paradigm to one of risk-based value generation. The study concludes that successful digital transformation requires a holistic integration of risk resilience mechanisms into the corporate DNA, where moving from a Defensive to a Transformational strategy necessitates an organizational evolution where risk management ceases to be a control function and becomes a strategic resource for navigating uncertainty.
Keywords: digital transformation; enterprise strategy; risk resilience; strategic typology; risk management integration; digital maturity; value creation